Dinosaur roar! - Stickland, Paul; Stickland, Henrietta (New York : Scholastic, 1997)
Illustrations and rhyming text present all kinds of dinosaurs, including ones that are sweet, grumpy, spiky, or lumpy.
On board pages.
Keywords: Children's stories